THE COURTESY CALL: STUDY ON POLITENESS OF FICTION CHARACTERS - Wijana, I Dewa Putu (Sanata Dharma University, 2020)
This research is an attempt to study politeness issues based on utturances of Osamu Dazaiâ€™s short story characters entitled â€œThe courtesy Callâ€, the EnglishÂ translation from Japanese â€œShinyu Kokanâ€ by Ivan Morris. Â By using politeness maxim theory proposed by Leech, it is found that the antagonistÂ often violatesÂ 6 politeness maxims which are tend to obey by the protagonist and his wife. The violation and the obedience of politeness maxims constitute a reflection of character differences intended by the writer. Utterances expressed by Fictionâ€™s characters are a rich source to exploit for studying politeness for pragmatic studies as their creation are based on careful observations of the author toward the world realities.